Home-based high-intensity interval training improves cardiorespiratory fitness: a systematic review and meta-analysis - Katsunori Tsuji; Yosuke Tsuchiya; Hisashi Ueda; Eisuke Ochi (BMC, 2023)
Abstract Background High-intensity interval training (HIIT) is an effective methods to improve maximal oxygen uptake. However, there is no definitive conclusion about the specific effectiveness of home-based HIIT. This review investigated the effects of home-based HIIT on cardiorespiratory fitness in a systematic review and meta-analysis. Methods Four electronic databases were searched (PubMed, Cochran database, Web of Science, Igaku Chuo Zasshi) for studies through March 25, 2023. Eligibility criteria include randomized controlled trials of home-based HIIT in adult people regardless disease or handicaped. Comparisons were made between non-exercise controls, laboratory-based HIIT, and moderate-intensity continuous training (MICT). The primary outcome was defined as cardiorespiratory fitness and the secondary outcome was defined as patient-reported outcomes. The standardized mean difference (SMD) with 95% confidence intervals (CIs) was calculated for quantitative indices. The random-effect model was used as the pooling method. Results Two hundred seven studies were identified, and 15 satisfied the inclusion criteria. The meta-analysis for cardiorespiratory fitness showed superiority of home-based HIIT to non-exercise controls (SMD 0.61, 95% CI: 0.21, 1.02). However, no significant difference in cardiorespiratory fitness was observed between home-based HIIT and lab-based HIIT (SMD: -0.35, 95%CI: -0.73, 0.03). Also, no significant difference was observed between the home-based HIIT and MICT (SMD 0.34, 95% CI: -0.05, 0.73). Conclusion These results indicated that home-based HIIT was an effective intervention for improving cardiorespiratory fitness in healthy adults and patients. Importantly, this review found no significant differences in cardiorespiratory fitness between home-based HIIT and the group of laboratory HIIT and MICT, highlighting its comparable effectiveness and potential as a practical and valuable exercise intervention.